PERAN PENDIDIKAN KEWARGANEGARAAN DALAM MEMBENTUK KARAKTER SISWA SEKOLAH DASAR - Adelsiana Lakapu; Fadil Mas’ud; Gupuh Rahayu; Ngurah Dharma Putra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Citizenship Education plays a strategic role in shaping the character of elementary school students. Amid rapid global changes, strengthening character education at the elementary level is essential to build the foundation of responsible and democratic future citizens. This article aims to analyze the contribution of Citizenship Education to the development of moral values, national identity, and social responsibility in elementary students. Using a systematic literature review approach, this article examines research published between 2015 and 2025 regarding the implementation of character education in primary schools through Citizenship Education. The analysis shows that Citizenship Education significantly strengthens students’ awareness of national values, moral reasoning, discipline, empathy, tolerance, and social responsibility. Effective learning models such as project-based learning, cooperative learning, contextual learning, and digital-based learning also enhance the internalization of character values. Teachers play an essential role as facilitators and role models in guiding students toward positive behaviors. This study underscores that Citizenship Education must be integrated comprehensively into learning processes and school culture to achieve optimal character development outcomes. Strengthening Citizenship Education in elementary schools is crucial to ensuring that students develop not only academic competencies but also strong character that aligns with Pancasila values.